FERTILITY ANALYSIS OF BUNGUS TELUK KABUNG WATERS BASED ON THE CONCENTRATIONS OF NITRATE, PHOSPHATE, AND THE ABUNDANCE OF PHYTOPLANKTON - Lazuardi, Andika; Nedi, Syahril; Siregar, Sofyan Husein (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
Water fertility is the capacity or ability of waters to provide suitable nutrients for the life of phytoplankton so that it can produce optimum production. This research was conducted on June 2021 in the Waters of Bungus Teluk Kabung, Padang, West Sumatra. The purpose of this study was to determine the fertility level of Bungus Teluk Kabung waters based on the concentration of nitrate, phosphate, and the abundance of phytoplankton. The results of this study show that the fertility rate of Bungus Teluk Kabung waters based on the value of nitrate concentration, phosphate, and phytoplankton abundance in the waters of Bungus Teluk Kabung, Padang, West Sumatra, belongs to the category of waters with low fertility levels (Oligotrophic) to moderate fertility levels (Mesotrophic). The concentration of nitrate and phosphate has a weak relationship with the abundance of phytoplankton in the waters of Bungus Teluk Kabung and there isn’t any significant effect between the concentration of nitrate and phosphate with the abundance of phytoplankton in the waters of Bungus Teluk Kabung, Padang, West Sumatra.